Synthesis and Characterization of Hetrocyclic Compounds Derived from ethyl-4-aminobenzoate - Ibraheem, Hiba H; Suhail, Khalida F; Hasan, Shaymaa S (Al-Nahrain Journal of Science, 2018)
New series of Schiff Bases were synthesized by many steps starting from treatment of ethyl-4-aminobenzoate with hydrazine hydrate to yield 4-aminobenzohydrazide (1) which was reacted with ethyl acetoacetate in ethanol to form pyrazole derivative (2) and this reacted with salicylaldehyde to yield azo compound (3). The azo compound condensation with appropriate amines (ethyl-4-aminobenzoate and 3-nitroaniline) to give new Schiff bases (4,5). The synthesized compounds were characterized by melting points, FTIR and 1HNMR.